Transcatheter edge-to-edge-repair of functional mitral regurgitation induces significant remodeling of mitral annular geometry - Paukovitsch, Michael; Felbel, Dominik; Jandek, Madeleine; Keßler, Mirjam; Rottbauer, Wolfgang; Markovic, Sinisa; Groeger, Matthias; Tadic, Marijana; Schneider, Leonhard Moritz (Frontiers in Cardiovascular Medicine, 2023)
Background: Mitral annular alterations in the context of heart failure often lead to severe functional mitral regurgitation (FMR), which should be treated with transcatheter edge-to-edge repair (M-TEER) according to current guidelines. M-TEER’s effects on mitral valve (MV) annular remodeling have not been well elucidated. Methods: 141 consecutive patients undergoing M-TEER for treatment of FMR were included in this investigation. Comprehensive intraprocedural transesophageal echocardiography was used to assess the acute effects of M-TEER on annular diameters. Results: Average patient age was 76.2±9.6 years and 46.1% were female patients. LV ejection fraction was reduced (37.0±13.7%) and all patients had mitral regurgitation (MR) grade ≥III. M-TEER achieved optimal MR reduction (MR≤I) in 78.6% of patients. Mitral annular anterior-posterior diameters (A-Pd) were reduced by -6.2±9.5% on average, whereas anterolateral-posteromedial diameters increased (3.7±8.9%). Overall, a reduction in MV annular areas was observed (2D: -1.8±13.1%; 3D: -2.7±13.7%), which strongly correlated with A-Pd reduction (2D: r=0.6, p<0.01; 3D: r=0.65, p<0.01). Patients that achieved A-Pd reduction above the median (≥6.3%) showed significantly lower rates of the composite endpoint rehospitalization for heart failure or all-cause mortality than those with less A-Pd reduction (9.9 vs. 28.6%, p=0.037, log-rank p=0.039). Furthermore, patients reaching the composite endpoint had an increase in annular area (2D: 3.0±15.4%; 3D: 1.9±15.3%), whereas those not reaching the endpoint showed a decrease (2D: -2.7±12.4%; 3D: -3.6±13.3%), although grade of residual MR after M-TEER was similar between these groups (p=0.57). In multivariate Cox regression adjusted for baseline MR, A-Pd reduction ≥6.3% remained a significant predictor of the combined endpoint (OR: 0.35, 95% CI: 0.14-0.85, p=0.02). Conclusion: Our findings indicate that effects of M-TEER in FMR are not limited to MR reduction, but also have significant impact on annular size. Moreover, A-Pd reduction, which mediates annular size reduction, has a significant impact on clinical outcome independent of residual MR.